How Classmates’ Gender Stereotypes Affect Students’ Math Self-Concepts: A Multilevel Analysis - Wolff, Fabian (Frontiers in Psychology, 2021)
The present research is the first to examine how students’ individual and their classmates’ math-related gender stereotypes, endorsing that math would be a typically male domain, relate to students’ math self-concepts. To this end, data of N = 1,424 secondary school students from Germany were analyzed using multilevel analyses. As expected, strong individual beliefs in the math-related gender stereotype were related to lower math self-concepts for girls, but to higher math self-concepts for boys. Moreover, classmates’ shared beliefs in this stereotype showed a negative relation to girls’ self-concepts, whereas no significant relation between classmates’ shared beliefs and boys’ self-concepts was found. These relations also persisted after controlling for students’ math grades and age. In sum, the results demonstrated that gender stereotypes shared by students’ classmates can have a substantial impact on students’ math self-concepts, beyond their individual gender stereotypes. This finding emphasizes the significance of classmates as important socializing peers in the process of students’ self-concept formation.